Optimal Prizes in Dynamic Elimination Contests: An Experimental Analysis - Rudi Stracke; Wolfgang Höchtl; Rudolf Kerschbamer; Uwe Sunde (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper investigates the effects of different prize structures on the effort choices of participants in two-stage elimination contests. A format with a single prize is shown to maximize total effort over both stages, but induces low effort in stage 1 and high effort in stage 2. By contrast, a format that allocates the same total amount to multiple prizes in such a way that the predicted effort remains constant across stages yields lower total effort provision. Experimental evidence suggests that (i) total effort is higher in the single prize format, but only for risk-neutral subjects; (ii) effort is constant across stages in the format with multiple prizes, independently of risk-attitudes; and (iii) the runner-up prize in the multiple prize format increases stage-1 and decreases stage-2 efforts in line with the theoretical prediction.
Keywords: C72; D72; J33; 330